(untitled) (Research, Society and Development, 2023)
The immune system is made up of an intricate network of organs, cells and molecules, and its main function is to maintain the homeostasis of the human body, fighting aggression in general. It consists of two groups of immunity, innate and adaptive. Faced with inconsistencies between studies, the present proposal is characterized by a narrative review that aimed to elucidate the hypotheses in the literature regarding the paradigm of the association between the immune response and the inflammatory process. This study is a narrative review with the purpose of discussing and describing the immune response and its relationship with inflammatory processes. The database: SciElo (Scientific Electronic Library Online) and PubMed (US National Library of Medicine) were used, with scientific data from October 2, 2022, with language restriction (Portuguese) and without restriction to the year of publication. The analyzed studies mainly addressed the inflammatory response. Inflammation starts in the microcirculation. It is there that I nourish the tissues of essential micronutrients and clean out unwanted waste. Microcirculation plays a valuable role in blood pressure. It is composed of arterioles, capillaries, and postcapillary venules. They are made up of a layer of collagen-lined endothelial cells. In short, lymphocytes act in the body as an important defense structure, interacting in a complex of cells and specific molecules, recognizing invading agents and preventing their action, maintaining its integrity and balance.